Unlocking key factors affecting utilization of biomass briquettes in Africa through SWOT and analytic hierarchy process: A case of Madagascar. (1st September 2022) - Yu, Shiwang; Lew, Vince; Ma, Wenting; Bao, Zhikang; Hao, Jian Li
Highlights: SWOT factors for biomass briquettes in Africa are identified. Analytic Hierarchy Process method is integrated into the SWOT factors. Empirical data is retrieved from three sectors. Strategies for utilizing sawdust biomass briquettes in the three sectors are given. Abstract: Due to environmental pollution caused by the excessive use of fossil fuels, developing countries are under considerable pressure to find sources of renewable and clean energy with limited financial resources and inadequate technological capacity. Bioenergy from briquetting sawdust, an organic waste by-product of the lumber industry, is one source of renewable and clean energy that is inexpensive to produce and does not require sophisticated technology. Since Madagascar's main industry is lumber, this study therefore set out to identify the key factors affecting the production and use of biomass sawdust briquettes in that country by integrating strengths, weaknesses, opportunities, threats (SWOT) analysis with a multi-criteria decision-making technique known as analytic hierarchy process (AHP). The results indicate that the most critical SWOT factors are lack of knowledge about biomass briquettes, lack of government support, political instability, social acceptance of biomass briquettes, focusing more on other types of renewable energy, and fossil fuel incentives. Suggestions are offered for how to promote the production and use of sawdust briquettes by overcoming critical weaknesses and coping with threats revealed in this study, including providing financial subsidies and tax breaks in Africa.